2019
DOI: 10.1038/s42003-018-0272-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological cholesterol depletion disturbs ciliogenesis and ciliary function in developing zebrafish

Abstract: Patients with an inherited inability to synthesize sufficient amounts of cholesterol develop congenital malformations of the skull, toes, kidney and heart. As development of these structures depends on functional cilia we investigated whether cholesterol regulates ciliogenesis through inhibition of hydroxymethylglutaryl-Coenzyme A reductase (HMG-CoA-R), the rate-limiting enzyme in cholesterol synthesis. HMG-CoA-R is efficiently inhibited by statins, a standard medication for hyperlipidemia. When zebrafish embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 68 publications
6
25
0
Order By: Relevance
“…Previous 9,20 and recent 38 reports have demonstrated that the structures induced by the overexpression of Prom1 have characteristics of the microvilli. Moreover, it has been shown that Prom1 resides also in other protrusive structures 15,21,39 including cytonemes 38 and cilia 40 , where cholesterol is an important ingredient 41,42 , and this fact is consistent with our current findings that cholesterol is essential for the fibre formation in RPE-like cells. However, our live-imaging analysis of the Prom1-transfected cells suggested that more types of membrane extensions can be formed by the overexpression of Prom1.…”
Section: Discussionsupporting
confidence: 93%
“…Previous 9,20 and recent 38 reports have demonstrated that the structures induced by the overexpression of Prom1 have characteristics of the microvilli. Moreover, it has been shown that Prom1 resides also in other protrusive structures 15,21,39 including cytonemes 38 and cilia 40 , where cholesterol is an important ingredient 41,42 , and this fact is consistent with our current findings that cholesterol is essential for the fibre formation in RPE-like cells. However, our live-imaging analysis of the Prom1-transfected cells suggested that more types of membrane extensions can be formed by the overexpression of Prom1.…”
Section: Discussionsupporting
confidence: 93%
“…We grew mycobacteria in the similarly hydrophobic but structurally distinct azide labeled phosphoethanolamine (Azido-PE, To test if host cholesterol facilitates PDIM spreading in vivo, we treated zebrafish with statins, drugs that inhibit HMG-CoA reductase, the rate-limiting step of cholesterol biosynthesis. Specifically, we used atorvastatin which was shown to lower cholesterol in zebrafish (Maerz et al, 2019). Following 24 h of treatment, atorvastatin decreased cholesterol levels in the larvae by 25%, and co-treatment with water-soluble cholesterol restored cholesterol levels ( Figure 8D).…”
Section: Host Cholesterol Promotes Pdim Spread and Mycobacterial Infementioning
confidence: 99%
“…The severe abnormalities associated with defects in cilia often include: neural tube and brain developmental defects, mental retardation, blindness, obesity, polydactyly and defects in the skeletal system, polycystic kidney and/or liver, infertility, situs inversus and airway infections 4 . These abnormalities in different organs reflect the wide range of cilia and their specialized functions in higher organisms 5,6 . However, more work is needed to further understand how mutations in genes encoding different subsets of centrosome/ciliary components lead to very different tissue abnormalities during development.…”
Section: Openmentioning
confidence: 99%